Fields of teaching and educational services - Green, John A. (New York : Harper & Row Publishers, Inc., 1966)
So insistent has been the plea for more teachers during the past decade that even the most uninformed citizen is probably aware of the gross need. But paradoxically it is only the sophisticated, professional educator who clearly understands the magnitude and profile of the teacher shortage. Few persons are aware of the fact that there is a serious imbalance in the supply of teachers: that there are fields of oversupply and others of cumulative, critical shortage. Furthermore, those who enter teacher preparation generally hold but a cursory concept of the classroom responsibilities of the teacher, with virtually no knowledge of the out-of-class responsibilities or of the numerous other administrative or service jobs which are available in the school system.
I. The Nature of and programs of preparation form teaching -- II. Academic teaching fields -- III. Special teaching fields -- IV. Service and administrative fields.
Includes bibliographical references and index.
Keywords: EDUCATIONAL COUNSELING